ASSESSMENT OF THE CURRENT STATUS OF THE CENOPOPULATIONS OF CALLIGONUM ALATUM LITW. IN THE FLOODPLAIN OF THE BAKANAS CANAL (Experimental biology, 2026)
The article reports that the first population of Calligonum alatum Litw.was identified in Almaty Region, Balkhash District, at a distance of 25 km from Bakanas village, within an area located 500–700 m from the Ili River. The site is situated in a gently undulating and hummocky terrain with sandy–gravelly soils. GPS coordinates of the study area were recorded as  N 44°41′12.0″, E 76°24′55.2″ Geobotanical investigations were conducted using standard field methods to assess population structure, species composition, and ecological conditions. Two cenopopulations were analyzed, where transects of 10 × 10 m² were established to study age structure, density, reproductive capacity, and spatial distribution. Within these plots, species composition, frequency of occurrence, and individual abundance were recorded, allowing for the calculation of population density and the development of an evaluation scale. Additionally, the vertical structure of vegetation cover and the percentage of projective cover were determined.
Keywords: geobotany, phytocenosis, population, cenopopulation, desert, transect